1994
DOI: 10.1002/eji.1830241131
|View full text |Cite
|
Sign up to set email alerts
|

CR1(CD35) and CR2(CD21) complement C3 receptors are expressed on normal human thymocytes and mediate infection of thymocytes with opsonized human immunodeficiency virus

Abstract: The present study demonstrates that the C3b receptor CR1 (CD35) and the C3dg/Epstein-Barr virus receptor CR2 (CD21) are expressed by 25% and 70% of normal human thymocytes, respectively. The expression of CR2 extends to both CD1+ and CD1- cells in the thymus. Two subsets of CR2+ thymocytes were defined expressing low and high density of the receptor. The CR2++ subset represented 20% of CR2+ thymocytes and co-expressed the CR1 receptor. CR2++ thymocytes expressed an immature CD1dull, CD3-, CD4dull, CD8-, CD7++ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…In addition, the observation that F97-6B3 mAb inhibited virus entry as well as OKB7 Ab suggests that other sites than SRC 1 and 2 are involved in the interactions between HIV and CRs. Inhibition of opsonized HIV infection by CD21 reagents have also been described in T cell lines [18,28], B cell lines [22][23][24] and thymocytes [25]. On B cell lines, Tremblay et al [22] have obtained a complete inhibition of the C'-ADE HIV infection with OKB7 whereas this antibody only induced a partial one in our normal B cells.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In addition, the observation that F97-6B3 mAb inhibited virus entry as well as OKB7 Ab suggests that other sites than SRC 1 and 2 are involved in the interactions between HIV and CRs. Inhibition of opsonized HIV infection by CD21 reagents have also been described in T cell lines [18,28], B cell lines [22][23][24] and thymocytes [25]. On B cell lines, Tremblay et al [22] have obtained a complete inhibition of the C'-ADE HIV infection with OKB7 whereas this antibody only induced a partial one in our normal B cells.…”
Section: Discussionmentioning
confidence: 72%
“…In spite of this activation and of virus opsonization, with anti-HIV antibodies and complement or complement only, HIV seems to be protected from human complement lytic action [17,10]. Non-lysed opsonized HIV may, thus, bind to complement receptors and infect CRs-bearing cells, as described on T cell lines [18], monocytic cell lines [19 21], B cell lines [22][23][24], thymocytes [25], primary monocytes [21], peripheral and tonsil B lymphocytes [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that retroviral infection of complement receptor-expressing cells can be enhanced by complement opsonization (2,5,12,13,16,21,26,28). Since mouse B cells express CR1 and CR2, prolonged interactions of B cells with C-opsonized virions are likely (16).…”
Section: Inoculation Of Isolated Igmentioning
confidence: 99%
“…However, other studies indicate that, although the levels of transcripts for CD21 are comparable between adult peripheral blood T and B cells (29), circulating adult T cells do not express detectable levels of membrane CD21 (29, this study). Still, up to 70% of normal human thymocytes express CD21 (30,31), and it has been suggested that CD21 could have a role in the proliferation and differentiation of T cells in the very early stages of maturation. Thus, the CD21 expression we observed on fetal/neonatal T cells could reflect the immaturity of the T-cell population, indicating recent emigration from the thymus.…”
mentioning
confidence: 99%